Analysis of Physics Kognitif Learning Outcomes of 11th Natural Sciences Grade State Senior High School 1 Alasa in Base-Online Learning - Bajongga Silaban; Parlindungan Sitorus; Ayunirmala Daryanti Zalukhu (Kasuari: Physics Education Journal (KPEJ), 2021)
Covid-19 has an influence  on education, which in the end the minister of education and culture issued letter a circular number  on 4th 2020, namely learning during the Covid-19 pandemic carried out online. This research aims to 1) describing cognitive learning outcomes of physics in based-online learning,” 2)  describing constraints of students on based-online learning in physics subjects matter, 3) calculate the magnitude of the correlation coefficient between cognitive physics learning outcomes with student constraints in based-online learning in physics subjects matter This research uses descriptive methods for collection are documents and questionnaires. Based on analysis of documentation and questionnaires obtained mean of the cognitive learning outcomes of  physics  11st Natural Sciences Grade State Senior High School Alasa is 48,00 was in the low category and the percentage of student constraints in online-based learning in physics subjects matter by 0,398 was in the high category and has a negative correlation between learning outcomes and student constraints in based-online learning in physics lessons with a correlation coefficient of -0,462. Be concluded that, if the constraints of students in based-online learning are low then the physics learning outcomes of students are high and otherwise.